Convergence or Parallel between Poll and Survey Research - Verapreyagura, Pornphan (Journal of Architectural/Planning Research and Studies (JARS), 2005)
Poll and survey research are the discourse representations or typicality of media texts. Although, they reflect the public opinion or the public thought about something or some phenomena, they are the parallel with convergence. They are not the permanent convergence or longitudinal parallel of each other. Their important cores consist of the representative principle, data principle, key informants, instruments, and data processing and analyzing. In the opposite, they are parallel about topic or research problem, background, objectives, benefits, the objectivity, and generalization. For reporting, poll and survey research are convergent by scientific techniques but parallel by language or rhetoric. Poll often uses mass media to represent its rhetoric of opinion in the public but survey research does not.